Sodium‐enriched nectar shapes plant–pollinator interactions in a subalpine meadow - Ethan VanValkenburg; Thiago Gonçalves Souza; Nathan J. Sanders; Paul CaraDonna (Ecology and Evolution, 2024)
Abstract Many plants have evolved nutrient rewards to attract pollinators to flowers, but most research has focused on the sugar content of floral nectar resources. Concentrations of sodium in floral nectar (a micronutrient in low concentrations in nectar) can vary substantially both among and within co‐occurring species. It is hypothesized that sodium concentrations in floral nectar might play an important and underappreciated role in plant–pollinator interactions, especially because many animals, including pollinators, are sodium limited in nature. Yet, the consequences of variation in sodium concentrations in floral nectar remain largely unexplored. Here, we investigate whether enriching floral nectar with sodium influences the composition, diversity, and frequency of plant–pollinator interactions. We experimentally enriched sodium concentrations in four plant species in a subalpine meadow in Colorado, USA. We found that flowers with sodium‐enriched nectar received more visits from a greater diversity of pollinators throughout the season. Different pollinator species foraged more frequently on flowers enriched with sodium and showed evidence of other changes to foraging behavior, including greater dietary evenness. These findings are consistent with the “salty nectar hypothesis,” providing evidence for the importance of sodium limitation in pollinators and suggesting that even small nectar constituents can shape plant–pollinator interactions.